Information technology in health care management - Lis, Tomasz (Technologia informacyjna w zarządzaniu jednostkami ochrony zdrowia, 2012)
Information and communication technology tools are nowadays present in each institution or business entity. They allow optimizing management. In the case of health care agencies, they also allow improving quality of medical services. The aforementioned tools are not only computers and software but also computer network or other external devices. Presently, in the age of the information society, on-line medical services via the Internet gained in importance. These services reduce costs of health centers functioning and simplify access to specialists, shorten waiting time for an appointment or treatment, allow making remote registration, remote examinations and treatments
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 60-72
Keywords: information technology; telemedicine; health care; technologia informacyjna; telemedycyna; ochrona zdrowia